Computation of Seepage through a Non-Homogeneous Earth Dam by Using (SEEP/W) Software - Issam, Rehamnia; Bachir, Benlaoukli; Abdelaziz, Rassoul; Arshad, Imran (PSM Biological Research, 2020)
In this research paper, a seepage flow through a non-homogeneous earth dam at various hydraulic heads was computed by using finite element-based software (SEEP/W) and the simulated results were compared with the field observation respectively. The research work was executed on a Fontaine Gazelles dam, which is an embankment dam situated at about 35 km, northeast of Biskra province, Algeria. The outcome of the simulated results showed that the dam is safe against piping for all the scenarios, at its original design as the installation of a cut-off wall found working effectively in reducing internal pore water pressure within the dam and its foundation. The overall maximum and minimum seepage flow was recorded at the pond level 383m (5.04920 LPS) and 374m (2.100 LPS) respectively. The performance efficiency of the model was founded as 99.924%. The RMSE, MAE, and AMRE were found (0.0342015 LPS), (0.00511668 LPS), and 1.06667% respectively; which indicates that there was no major variation between observed and simulated seepage values.